KRITIK SOSIAL DALAM KOMIK STRIP PAK BEI - Novriansyah, Yudhi (JURNAL ILMU SOSIAL, 2006)
This research aimed to do interpret the marking which flange social criticism and know laboring ideology in story of Comic Strip Pak Bei. Research based on theory of structural semiotic according to Ferdinand De Saussure. Using analysis of Syntagmatic as first level of meaning to the text network and also picture, and analysis of Paradigmatic as second level of meaning or implicit meaning (connota-tion, myth, ideology) Analysis done to six Comic choice edition of Strip Pak Bei period of November 2004 - Februari 2005 which tend to flange social criticism. At band of syntagmatic, result of research indicate that story theme lifted from social problems that happened in major society. The fact clear progressively when connected by Intertextual with information and texts which have preexisted. At band of Paradigmatic, social criticism tend to emerge dimly, is not transparent. Because of Comic Strip Pak Bei expand in the middle of Java cultural domination that developing myth of criticize as action menacing compatibility and orderliness of society. Story of Comic Strip Pak Bei also confirm dominant ideology in Java society culture, namely ideology of Patriarkhi and Feudalism which still go into effect until now. This prove ideology idea according to Louis Althusser which not again opposition between class, but have been owned and practiced by all social class.